The Tragedy of Hoemdiplet: Freud’s Fusion of Oedipus and Hamlet - Armstrong, Richard H. (CODEX - Revista de Estudos Clássicos, 2018)
Very early on, Freud centered his argument for the universality of the Oedipus complex on a reading of Oedipus Tyrannus. But why did he insist on reading it specifically as a theatrical experience on the part of a modern audience? This article argues that Freud’s theory from the start had fused the Sophoclean play with Shakespeare’s Hamlet, deploying Oedipus Tyrannus metatheatrically as Hamlet deployed “The Murder of Gonzago” to trigger a reaction in Claudius. Freud puts us in the audience of Oedipusin order for us to sense our own oedipal guilt, confirming his theory.